Analyzing Policymaking for Tuberculosis Control in Nigeria - Nura M. R. Ahmad; Cristina Montañola-Sales; Clara Prats; Mustapha Musa; Daniel López; Josep Casanovas-Garcia (Complexity)
Today, tuberculosis (TB) is still one of the major threats to humankind, being the first cause of death by an infectious disease worldwide. TB is a communicable chronic disease that every year affects 10 million people and kills almost 2 million people in the world. The main key factors fueling the disease are the progressive urbanization of the population and poverty-related socioeconomic factors. Moreover, the lack of effective tools for TB diagnosis, prevention, and treatment has decisively contributed to the lack of an effective model to predict TB spread. In Nigeria, the rapid urbanization along with unprecedented population growth is causing TB to be endemic. This paper proposes a mathematical model to evaluate TB burden in Nigeria by using data obtained from the local TB control program in the community. This research aims to point out effective strategies that could be used to effectively reduce TB burden and death due to TB in this country at different levels. The study shows that efforts should be oriented to more active case finding rather than increasing the treatment effectiveness only. It also reveals that the persistence of the disease is related to a large number of latently infected individuals and quantifies the lives that could be saved by increasing the notification rate using active case finding strategy. We conclude that undiagnosis is the bottleneck that needs to be overcome in addition to the incorporation, improvement, and/or strengthening of treatment management and other essential TB control measures in Nigeria.